Self-efficacy among kindergarten teachers in Sulaimani - Mahmoud, Soma Kamil Mahmoud; Mohammed, Asst.Prof.DrAbdulsamad Ahmed Mohammed (Sulaimani Journal for Humanities, 2025)
The aim of this research is to ascertain the level of self-efficacy among kindergarten teachers, to determine the differences in the level of self-efficacy according to the variables of gender (male - female), years of service, educational qualification, the type of kindergarten (public and private) . The research population consisted of all kindergarten teachers in the city of Sulaimani for the academic year 2024-2025 who were actively working, numbering (1222) teachers, (125) male teachers and (1097) female teachers. The study sample comprised (412) teachers of both genders, selected using a simple random method. The instrument used was the self-efficacy scale, which the researchers prepared by drawing upon previous studies. The results indicated that self-efficacy among kindergarten teachers is at a high level. There was no statistically significant difference in the level of self-efficacy according to the variables of gender.
Keywords: Self; SelfEfficacy; Kindergarten Teacher; Kindergarten